2004
DOI: 10.1118/1.1758351
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric properties of radiophotoluminescent glass rod detector in high‐energy photon beams from a linear accelerator and Cyber‐Knife

Abstract: A fully automatic radiophotoluminescent glass rod dosimeter (GRD) system has recently become commercially available. This article discusses the dosimetric properties of the GRD including uniformity and reproducibility of signal, dose linearity, and energy and directional dependence in high-energy photon beams. In addition, energy response is measured in electron beams. The uniformity and reproducibility of the signal from 50 GRDs using a 60Co beam are both +/- 1.1% (one standard deviation). Good dose linearity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 16 publications
4
62
0
Order By: Relevance
“…[3][4][5] In some studies, the RGD has been evaluated using high energy radiotherapy photon beams. 4,[7][8][9] Tuda et al reported that its reproducibility of dose for high-energy x rays was 0.82% in coefficient of variance (CV), which is comparable to that of a TLD. As for energy dependence of the dose response, the mass energy absorption coefficient of the RGD, silveractivated metaphosphate, is several times higher than that of the TLD, LiF, for low-energy photons around 25 keV.…”
Section: Introductionmentioning
confidence: 85%
“…[3][4][5] In some studies, the RGD has been evaluated using high energy radiotherapy photon beams. 4,[7][8][9] Tuda et al reported that its reproducibility of dose for high-energy x rays was 0.82% in coefficient of variance (CV), which is comparable to that of a TLD. As for energy dependence of the dose response, the mass energy absorption coefficient of the RGD, silveractivated metaphosphate, is several times higher than that of the TLD, LiF, for low-energy photons around 25 keV.…”
Section: Introductionmentioning
confidence: 85%
“…When these centers receive 337.1 nm pulsed ultraviolet laser beam of the readout system, they will be excited. They will return to a stable energy level after emitting an orange radiophotoluminescent (RPL) (Piesch et al, 1986(Piesch et al, , 1990Araki et al, 2004). The luminescent intensity of an ultraviolet pulse excitation is proportional to the exposure dose of the radiation.…”
Section: Dosemeters and Instrumentsmentioning
confidence: 99%
“…The advantages of the RPLGD compared to the thermoluminescence dosimeter (TLD) include good reproducibility of 1% and relatively low energy dependency at energies higher than 200 keV [8][9][10]. In addition, the RPLGD has a relatively small incident-beam-angle dependency and a low toxicity inside a human body compared to the TLD or the optically-stimulated luminescence dosimeter [11][12][13].…”
Section: Calibration Of the Radio-photoluminescence Glass Dosimetermentioning
confidence: 99%